Evaluation of the Immune Response in AI Vaccinated Broiler Chickens: Effect of Biosecurity Faults on Immune Response - Ka-Oud, H.A.; Zakia, M.A.; Kamel, Mervat M. (International Journal of Poultry Science, 2008)
This article was a trial to evaluate: The immune responses of broiler chickens vaccinated with common AI commercial vaccines in Egypt and the effect of the applied biosecurity measures on the immune response of vaccinated chickens. The results revealed that: There were high to moderate levels of maternal immunity against AIV (H5N1and H5N2) on the 1st, 5th day of age and low levels on the 7th day of age. There was no significant difference concerning the immune response of H5N1 and H5N2 AI vaccines (P < 0.05) in vaccinated broilers. Vaccination at 10-days of age with 0.5ml of vaccine, gave satisfactory titers, on the 3rd week post vaccination. By the 4th week post vaccination chickens exhibited highest titers and continued to the 5th week post vaccination. Mortality rate was relatively higher in flocks have been given vaccine at the age of 5 days specially H5N1 vaccine (Mortality rates were 1%, 0.5 and 1%, 0.2% in the 1st and 2nd week post vaccination respectively) than those have been given at the age of 10 days (Mortality rates were 0.5%, 0.1% in both 1st and 2nd weeks post vaccination respectively). The relationships between the major components of biosecurity and immune response of vaccinated chickens revealed: 1. There was a significant correlation between HI titer and the distance between farms (r = 0.72, P < 0.05) 2. There was a significant difference between broiler houses of incorrect microclimatic conditions( Moisture content of litter, Air temperature, Air relative humidity) and immune response of broilers vaccinated against AIV (P < 0.05). The association between biosecurity faults as risk factors in broiler house and their effects on HI titers in chickens vaccinated against AIV revealed that, there was an association between faults of biosecurity measurements (Mal-biosecurity measures) and the low value in HI titer of chicken sera vaccinated against AIV vaccines.